Peningkatan Kemampuan Bercerita Tenaga Medis Sebagai Bentuk Profesionalisme Pelayanan Terhadap Hospitalisasi Pasien Anak - Ari Setyorini; Masulah Masulah (Universitas Muhammadiyah Surabaya, 2017)
This article aims at describing the story telling training process for the medical professionals in Muhammadiyah Hospital of Surabaya and Siti Khodijah Hospital of Sidoarjo. Based on the preliminary study, the training is one of the best solutions to enhance the hospiltals’ professional service since the hospitals face similar problem of hospitalization. Other than that, the service is particularly for the pediatric patients who suffer psychological trauma of hospitalization. The training was carried out through three stages of pre-activity, activity, and evaluation. Through the comparison between pre and post-training test toward the trained pediatric nurses of Muhammadiyah Hospital of Surabaya, the result confirmed that the mean of the post-training score was increased significantly from 55.8(pre-training score) to 84 (post-training score). The second result which is got from the pediatric nurses of Siti Khodijah Hospital shows the sharp increase. The mean of pre-training score was 39.9, and the mean of the post-training score was 88.8. Through interviewing with the participants and the managements of both hospitals, it can be concluded that the training gained positive responses from the hospital management, the pediatric nurses and the patients as well.